SPAIN AS AN ATTRACTIVE PLACE FOR FOREIGN INVESTMENT - Anatolii O. Zadoia; Khrystyna S. Yavtushynska (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The aim of this paper is to examine the Spanish economy, identify key areas for investment and assess the risks and opportunities associated with this. The article examines all aspects related to determining the degree of investment attractiveness of Spain, as well as the current state of the Spanish investment environment and the latest trends in the Spanish investment sector. Other objectives of this study include examining the Spanish economy, identifying key areas for investment and current trends in potential investment. An analysis of the threats and opportunities associated with investing in Spain was also conducted. Various resources have been used to provide reliable, up-to-date, in-depth, detailed and comprehensive analysis. First, the world’s leading databases, such as the World Bank, the International Monetary Fund, UNCTAD, and so on. Second, data from Spanish government and financial institutions were taken into account. In order to study the problem from different angles, the media, scientific papers and journals were also involved in gathering the necessary information. The analysis allowed us to identify the most significant advantages of the Spanish economy as an object of investment, in particular: – highly developed service sectors, such as financial and insurance services, telecommunications, D&R, etc., which are constantly fueled by FDI inflows; – strategic location and opportunity to enter the EU market; – successful internal structural reforms have been implemented, which have led to increased labor flexibility; – favorable conditions for immigration (including labor immigration); – leading positions in terms of solvency and trust; – economic openness of the country and its participation in a large number of international trade agreements; – measures taken to weaken business and investment regulation; – non-interference of the state in business, fair competition and not perverted trade; – excellent infrastructure that stimulates economic growth; – one of the most innovative and efficient tax agencies – AEAT; – absence of other significant socio-economic, legal and criminal risks that hinder investment. Although Spain faces high unemployment, the current economic crisis caused by the Crown virus, and huge public debt, most of them can be turned into the benefits of foreign investment projects. Similarly, to overcome the economic crisis, the country needs an influx of money from outside, so now the conditions for foreign investors are even more favorable